2021
DOI: 10.1001/jamanetworkopen.2021.33877
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions of Multidisciplinary Cancer Care Clinicians Toward Telehealth and Secure Messages

Abstract: Key Points Question What are the perceptions and experiences of multidisciplinary cancer care clinicians (medical oncologists, radiation oncologists, surgical oncologists, oncology navigators, and cancer survivorship) with regard to telehealth visits and exchanging secure messages with patients during the COVID-19 pandemic? Findings In this survey study of 202 multidisciplinary cancer care clinicians, most were satisfied with telehealth and wished to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…16,18,19 Live interpreter support is available to all patients and providers using KPNC's telehealth services (both phone and video visits). Throughout the study period, no new oncology clinics or hospitals were opened, acquired, or closed by KPNC, the total number of oncology providers was stable around 128 20 and did not significantly change, and the number of adult KPNC members has changed by < 2% (internal unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…16,18,19 Live interpreter support is available to all patients and providers using KPNC's telehealth services (both phone and video visits). Throughout the study period, no new oncology clinics or hospitals were opened, acquired, or closed by KPNC, the total number of oncology providers was stable around 128 20 and did not significantly change, and the number of adult KPNC members has changed by < 2% (internal unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…The Consult Station booth is the first telemedicine device enabling completely remote medical teleconsultation with concurrent collection of clinical parameters, as otherwise teleconsultations are often limited to telephone consultations [ 24 - 26 ]. With real-time measurement of several medical parameters, the use of diagnostic tools, and video consultations, Consult Station is a good option when face-to-face consultations are not possible [ 26 ]. The COVID-19 pandemic contributed to an acceleration of teleconsultation acceptance and to the restructuring of pre-existing telehealth care devices or pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluating oncology providers’ opinions of virtual care focus on perceptions of virtual visits. Recent studies before and during the COVID-19 pandemic show that most oncologists have a favorable opinion of virtual visits 2,25,68,69 . An ASCO survey conducted in late 2020 found that 92% of providers would like to continue telehealth as part of their practice, and 64% of providers felt the quality of care with virtual visits was similar to in-person visits 70 .…”
Section: Virtual Care In Oncologymentioning
confidence: 99%
“…Providers felt that virtual visits are more appropriate for certain types of visits such as survivorship and symptom management and less appropriate for postsurgery/radiation visits, initial visits, and goals-of-care conversations. 69 Virtual care has allowed oncology providers to increase remote collaboration with other providers. Secure email is an established communication tool for provider collaboration; however, these messages frequently occur outside health records and are not captured, causing data fragmentation.…”
Section: Provider Experiencementioning
confidence: 99%
See 1 more Smart Citation